(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A new Iberian inscription in the southern variety of the Palaeohispanic scripts has been found in the archaeological site of Cerro de la Mesa (Alcolea de Tajo, Toledo). This paper provides an edition and a study of this inscription.